An analysis on forced eruption in crown lengthening of un-restorable teeth - Vahid A (Tehran University of Medical Sciences, 2004)
Cervical third root defects, like perforations (due to resoption or iatrogeic), fractures or invasive decays make great difficulties for appropriate restoration making. In these circumstances crown lengthening is needed, especially for anterior teeth. Forced eruption also could be a beneficial treatment. By this therapy, cervical third root defects will be available to receive a good restoration. without gum and biologic width problems. In this article tried to introduce this method of therapy by reviewing litraure and with regard to personal research.